Development of an analytical method for the determination of pesticides in tropical fruits by LC-QTOF-MS/MS after QuEChERS extraction sample cleanup and DLLME preconcentration - Sel, Sabriye; Er, Elif Ozturk; Koyuncu, Ikbal (IOP Publishing Ltd, 2024)
In this study, QuEChERS extraction was combined with dispersive liquid-liquid microextraction (DLLME) to extract pesticides from tropical fruits for determination by a highly accurate and sensitive liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-QTOF-MS/MS) system. The QuEChERS method served as a matrix clean-up tool and the DLLME method preconcentrated the analytes for their determination at trace levels. All parameter variables of the DLLME method were optimized to improve the extraction output and lower the limits of detection and quantification (LOD and LOQ) for all the analytes. Under the optimum experimental conditions, the LOD and LOQ values were found in the range of 0.004-0.013 and 0.27-0.61 mu g l-1, respectively. The detection limits achieved by direct LC-QTOF-MS/MS analysis were increased by about 10-260 folds using the optimized DLLME method. To assess the accuracy and applicability of the developed method, spike recovery experiments on tropical fruits were carried out. The matrix matching calibration method was used to enhance the quantification accuracy of the analytes in kiwi, pineapple, and mango matrices, with percent recoveries ranging between 89 and 117%.
Keywords: dispersive liquid-liquid microextraction; QuEChERS; pesticide residue; LC-QTOF-MS/MS; LIQUID-PHASE MICROEXTRACTION; TANDEM MASS-SPECTROMETRY; ORGANOCHLORINE PESTICIDES; GAS-CHROMATOGRAPHY; RESIDUES; VEGETABLES; SULFATE; Chemistry